Factors affecting growth and internationalization of micro-enterprises in a sparsely populated region: Case South Savo, Finland - Timo Partala; Sami Jantunen; Tommi Kuukkanen; Helena Merikoski (Journal of Innovation and Entrepreneurship, 2024)
Micro-enterprises have recently received increased research attention due to their contribution to economic growth and employment, and an increasing amount of research has focused on studying their performance. The current objective was to study factors affecting the growth and internationalization of micro-enterprises, as well as the most important barriers for growth in the sparsely populated region of South Savo in Finland. Owners or managers of 108 micro-enterprises responded to a questionnaire probing variables representing aspects of growth, internationalization, innovation, networking, digital maturity, and business environment, among others. Statistical analyses including multiple regressions were used to analyze the data collected on quantitative rating scales. The results suggested that intention to grow and level of networking with other companies and public actors were directly related to actualized growth. Intention to grow was, in turn, affected by innovativeness, growth capability, intention for internationalization, and business environment. In addition, the level of innovativeness and intention for internationalization were related to actual level of internationalization. The most important barriers for growth selected by the participants were lack of time for development activities, threshold to hire new employees, and sufficiency of funding. The results were utilized in guiding regional development activities in the South Savo region.
Keywords: 650; Growth; Innovativeness; Internationalization; Micro-enterprise; Networking